2012
DOI: 10.1186/1477-7819-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 overexpression and poor clinical outcomes in Taiwanese oral cavity squamous cell carcinoma

Abstract: BackgroundCyclin D1 gene regulates cell cycle and plays an important role in the tumorigenesis of human cancers. The association between cyclin D1, clinicopathologic parameters and prognosis in oral cavity squamous cell carcinoma (OSCC) is inconclusive.MethodsA total of 264 male OSCCs were examined for cyclin D1 protein expression using immunohistochemistry (IHC). The expression levels of cyclin D1 were defined as overexpression when more than 10% of tumor cells displayed nuclear staining with moderate to stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 23 publications
9
57
0
1
Order By: Relevance
“…13 Previous clinical investigations have shown that OSCC survival is significantly influenced by the level of cyclin D1 expression, and over 30% of the studied OSCC tissue samples showed overexpression of cyclin D1 protein. [14][15][16] The high level of cyclin D1 mRNA may be because of enhanced transcription or mRNA stabilization. Transcription of cyclin D1 is controlled by several transcription factors, including STAT3/5A, nuclear factor kappa B (NFkB), ETS1, and AP1.…”
Section: Discussionmentioning
confidence: 99%
“…13 Previous clinical investigations have shown that OSCC survival is significantly influenced by the level of cyclin D1 expression, and over 30% of the studied OSCC tissue samples showed overexpression of cyclin D1 protein. [14][15][16] The high level of cyclin D1 mRNA may be because of enhanced transcription or mRNA stabilization. Transcription of cyclin D1 is controlled by several transcription factors, including STAT3/5A, nuclear factor kappa B (NFkB), ETS1, and AP1.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein (HSP)A4, also known as HSP70, has been shown to be significantly associated with low differentiation and poor prognosis in a number of malignant tumors (17)(18)(19). CCND1, also known as cyclin D1, is overexpressed in several human tumors; its expression is induced by growth factors and occurs at multiple levels, including increased transcription, translation and protein stability (20)(21)(22). Cyclin D1 plays an important role in G1 phase transition, which is a kinase-independent function, by sequestering cyclin-dependent kinase (CDK) inhibitors, such as CDKN1A (p21) and CDKN1B (p27) for the efficient activation of CDK2-containing complexes (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although increased expression of cyclin D1 in OSCC has been reported, there are controversial data on the prognostic value of cyclin D1 overexpression in OSCC. Some studies suggest that increased expression of cyclin D1 is associated with poor survival (12–16), while other studies demonstrate that cyclin D1 overexpression provides little prognostic information for patients with OSCC (17,18). …”
Section: Introductionmentioning
confidence: 99%